O-132 Sustained efficacy and safety of relugolix combination therapy in women with endometriosis-associated pain: SPIRIT 52-week data. (6th August 2021) - As-Sanie, S; Giudice, L; Abrao, M S; Wilk, K; Mehedintu, C; Becker, C; Arjona Ferreira, J C; Wagman, R B; Wang, F; Warsi, Q A; Neil, J
Abstract: Study question: To assess the long-term (52-week) efficacy and safety of relugolix combination therapy (Relugolix-CT) in the treatment of endometriosis-associated pain. Summary answer: Relugolix-CT demonstrated a sustained improvement of endometriosis-associated pain and maintenance of bone mineral density (BMD) over the extension treatment period. It was well tolerated. What is known already: Endometriosis is a chronic condition characterized by symptoms of menstrual and non-menstrual pain, and dyspareunia, which have a substantial impact on women's lives. SPIRIT 1 and 2 were Phase 3, randomized, double-blind, placebo-controlled studies of once-daily Relugolix-CT (relugolix 40 mg, estradiol 1 mg, norethindrone acetate 0.5 mg) in premenopausal women (age 18–50 years) with surgically diagnosed endometriosis and moderate-to-severe dysmenorrhea and non-menstrual pelvic pain (NMPP) at baseline. These trials demonstrated a significant improvement of dysmenorrhea, NMPP and dyspareunia in women treated with Relugolix-CT, with a minimal decline in BMD vs placebo over 24 weeks. Study design, size, duration: Women who completed the 24-week pivotal studies (SPIRIT 1 and 2 trials) were eligible to enroll in an open-label, single-arm, long-term safety and efficacy extension study for an additional 80 weeks. All women received once-daily oral Relugolix-CT. Analyses were done based on original randomization in pivotal studies: Relugolix-CT, delayed Relugolix-CT (relugolix 40 mg alone for 12 weeks, then Relugolix-CT for 12 weeks), or placebo. Here, 52-week efficacy and safety outcomes are presented. Participants/materials, setting, methods: The primary endpoints were the proportion of dysmenorrhea and NMPP responders at Week 52, based on daily Numerical Rating Scale (NRS) scores (0=no pain, 10=worst pain imaginable). A responder was a woman who achieved a predefined, clinically meaningful reduction from baseline in NRS score with no increase in analgesic use. Secondary efficacy endpoints included change in Endometriosis Health Profile-30 (EHP-30) pain domain scores, and analgesic/opioid use. Safety endpoints included adverse events (AEs) and BMD evaluation. Main results and the role of chance: Of 1261 randomized patients, 1044 completed the primary studies; 802 enrolled in the long-term extension and 681 completed 52 weeks of treatment. Baseline demographics and clinical characteristics of the extension population were consistent with those of the original randomized population. Sustained improvement of endometriosis-associated pain was demonstrated with Relugolix-CT through 52 weeks, the proportion of responders for dysmenorrhea was 84.8% and 73.3% for NMPP. NRS least squares (LS) mean scores for dysmenorrhea and NMPP decreased from 7.4 (severe) and 6.0 (moderate) at SPIRIT study baseline to 1.3 (mild) and 2.2 (mild) at Week 52, equating to 82.8% and 62.9% reduction in dysmenorrhea and NMPP, respectively. Mean NRS for dyspareunia decreased from 5.9 (moderate) to 2.4 (mild), demonstrating 60.1% reduction with Relugolix-CT. Daily functioning measured by the EHP-30 pain domain score was improved (–38.1 point) and the majority of women (85.6%) were opioid-free at Week 52. There was no disproportionate increase in the incidence of AEs in the Relugolix-CT group with no new safety signals identified through the 52 weeks. BMD was preserved over the extension period with overall LS mean change from baseline to Week 52 of –0.83% (95% CI: –1.34, –0.32) for lumbar spine in the Relugolix-CT group. Limitations, reasons for caution: The study was conducted as an open-label study without a control group over the 28 weeks of the extension period. Wider implications of the findings: Relugolix-CT demonstrated a sustained improvement of dysmenorrhea, NMPP, and dyspareunia, and reduced pain-related functional limitations and the need for opioids over 52 weeks in women with moderate-to-severe endometriosis-associated pain. Relugolix-CT was generally well tolerated and associated with minimal BMD loss after treatment initiation followed by BMD maintenance over 52 weeks. Trial registration number: NCT03654274